Environmental sustainability of future aquaculture production: analysis of Singaporean and Norwegian policies - Bohnes, Florence Alexia (2022)
To address global food demand and sustainability challenges, aquaculture has appeared as an essential element in food systems, and an increasing number of national aquaculture policies have emerged over the past decades. However, several of these policies have failed because of an often-argued inability to anticipate their far-reaching implications on environmental and socio-economic variables. To tackle this gap, we propose a step-wise framework to assess the national environmental impacts from aquaculture industries with a prospective and systemic approach. Starting from identifying policy-based national targets, the methodology relies on economic equilibrium modeling to develop realistic future-oriented scenarios of the aquaculture sector, and couples them with life cycle assessment principles. To evidence its operability, we apply the framework to two distinct case countries: Norway and Singapore. Beyond our key findings from the analyses of the policies in both countries, we observed that feed production and usage are important drivers of impacts, hence calling for new and more environmentally-friendly feed options. Our results additionally show that the development of aquaculture following existing governmental policies may not directly reduce greenhouse gases emissions and, hence, not support climate change mitigation objectives. These findings should however be cautioned as potential shifts of diets due to the increasing seafood availability might occur, leading to indirect environmental benefits. We therefore advocate the further expansion of our framework to cover the entire food system, so it can integrate such indirect effects. Meanwhile, we recommend its interim application to support policy-making and help move towards more environmentally sustainable aquaculture systems.